Extracellular Vesicles in Herpes Viral Spread and Immune Evasion - Bello-Morales, Raquel; López-Guerrero, José Antonio (Frontiers in Microbiology, 2018)
Extracellular vesicles (EVs) are involved in numerous processes during infections by both enveloped and non-enveloped viruses. Among them, herpes simplex virus type-1 (HSV-1) modulates secretory pathways, allowing EVs to exit infected cells. Many characteristics regarding the mechanisms of viral spread are still unidentified, and as such, secreted vesicles are promising candidates due to their role in intercellular communications during viral infection. Another relevant role for EVs is to protect virions from the action of neutralizing antibodies, thus increasing their stability within the host during hematogenous spread. Recent studies have suggested the participation of EVs in HSV-1 spread, wherein virion-containing microvesicles released by infected cells were endocytosed by naïve cells, leading to a productive infection. This suggests that HSV-1 might use microvesicles to expand its tropism and evade the host immune response. In this review, we briefly describe the current knowledge about the involvement of EVs in viral infections in general, with a specific focus on recent research into their role in HSV-1 spread. Implications of the autophagic pathway in the biogenesis and secretion of EVs will also be discussed.